Computing hardware analysis for Agents of Things (AoT) applications - Mzahm A.M.; Ahmad M.S.; Tang A.Y.C. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer hardware; Computer software; Software agents; Comprehensive analysis; Computing hardware; Computing resource; Hardware and software; Hardware devices; Novel concept; Optimum Reseaning Level; Value added service; Hardware